COVID-19 vaccination among cirrhotics in Italy: High coverage and effectiveness of 3 doses versus 2 in preventing breakthrough infection and hospitalization. Issue 3 (March 2023) - Stroffolini, Tommaso; Ciancio, Alessia; Federico, Alessandro; Benigno, Rosa G.; Colloredo, Guido; Lombardi, Anna; Niro, Grazia Anna; Verucchi, Gabriella; Ferrigno, Luigina; Gioli, Federico; Marignani, Massimo
Abstract: Background and Aims: Few reports, all retrospective, have evaluated vaccine coverage against COVID-19 infection in cirrhotic subjects. No data are available for European Countries. We aimed to explore this topic and potential independent predictors of lack of vaccination. Methods: Between January 1st and June 30th 2022, 1512 cirrhotic subjects of any etiology were consecutively enrolled in an observational - prospective study in 8 referral centers in Italy. Adjusted Odds Ratios (O.R.) for the association with lack of vaccination and with occurrence of breakthrough infection were evaluated by multiple logistic regression analysis. Results: Overall vaccine coverage was 89.7% (80% among people born abroad). Among the 1358 vaccinated people, 178 (13.1%) had a breakthrough infection; of them 12 (6.7%) were hospitalized, but none died. Independent predictors associated with lack of vaccination were birth abroad, age <65 years and lower years of schooling. Child stage B/C was the only independent predictor of breakthrough infection. Occurrence of breakthrough infection was more likely reported in subjects who received 2 doses of vaccine than in those who received 3 doses (33.9% versus 9.0%; P <0.001). Conclusion: High vaccine coverage against COVID-19 infection is observed among cirrhotic subjects in Italy. Vaccine is effective in preventing severe outcomes. Three doses are more effective than two, even in cirrhotic subjects. Lay Summary: This large cohort study evidenced high vaccine coverage against COVID-19 infection among cirrhotic subjects in a European country and the effectiveness of vaccine in preventing severe outcomes. Three doses of vaccine are more effective than two in preventing breakthrough infection and hospitalization. Informative campaigns targeting people younger than 65 years of age and those with lower years of schooling may increase these excellent results.